Réponses

  • Utilisateur Brainly
2013-10-22T13:41:19+02:00
Calculer les expressions
A= (1/2+7/8)*8/11
   =(4/8+7/8)*8/11
   =(4+7)/11
   =1

B= 7/5-25/7+7/10
  =49/35-125/35+7/10
  =-76/35+7/10
  =-152/70+49/70
  =-103/70

C= 2-8/3*8/5
  =2-64/15
  =30/15-64/15
  =-34/15

D= -7/-8-5/8*5

  =7/8-25/8
  =-18/8
  =-9/4
2013-10-22T13:44:07+02:00
A = ( 1/2 + 7/8 ) * 8/11
= 11/8 * 8/11
= 1

B = 7/5 - 25/7 + 7/10
= -76/35 + 7/10
= -103/70

C =  2 - 8/3 * 8/5
= 2 - 64/15
= -34/15

D = -7/-8 - 5/8 * 5
= -7/-8 - 25/8
= -9/4 ou -2,25